PELAKSANAAN PENYITAAN BARANG BUKTI DAN HAMBATANNYA YANG DILAKUKAN OLEH PENYIDIK POLRI DALAM PRAKTEK - Ibnu Riza (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT            Process or seizure procedures of evidence in the case criminal is as follows : Before doing his job, the officer or investigator is required to obtain a license in advance from Chairman of the local Court except in a state that is very necessary and urgent; Showed his ID to the person from whom the object was confiscated; Authorities ordered the man who controls the object to be seized to be handed to him on a letter or posts originating from the suspect, shown to him, his or intended to be, or tools for committing a crime; Shows the object to be seized on the person of which the object was confiscated or his family and mark the items in the presence of the head of the village or neighborhood leaders with two witnesses; Make an official report of seizure, after read out then given a date, signed by the investigator, the person concerned or his family and two witnesses; Before the object or seized objects are included in the state confiscated items storage, it should be noted in advance about the weight or amount according to their kind, traits or characteristics of the object, place, day and seized dates, where the identity of the object was confiscated then wrapped, labeled and office stamp and signed by the investigator; For security interests when deemed necessary to shoot first. Some of the obstacles encountered by investigators in conducting seizure among others : Evidence are no longer intact or damaged; Evidence transferable to others; Evidence entered another entity; Collateral evidence made at the Pawnshop; Missing evidence was not found. Attempts by investigators overcoming these obstacles, among others : If the evidence transferable to others, then make D.P.O (Person Searches List) and D.P.B (Search List Item) sent to the ranks of the Police : if the evidence entered another entity, then to approach and unity where the evidence is located, by way of telling someone to buy the evidence in the hope that evidence may be out of the unity of regions and used as evidence; if the mortgaged evidence, then Police confiscate the evidence by asking the approval of foreclosure to the District Court in a decision of the District Court, then the pawnshop submit the evidence, although have to argue; If the missing evidence was not found, then investigator conducting an investigation on T.K.P (The Crime Scene); Finding statements of witnesses and suspects by collecting witnesses and suspect     to find the truth of evidence no longer shaped like jewelry that has been melted by the buyer. Keywords : object evidence,investigator POLRI